(3GNJdGa CbhGd eGdc hCUMGHgs - (3jhSa Hf YHO Gddg Hf YHO GdHQ GdfeQj GdbQWHj GdeGdcj, GHf YHO GdHQ , CHh YeQ , J (B463 (3g` s
(3ChdgG (B:s
(3GdMeO ddg caGA eG CfYe gPG cJGH CPcQ ajg Ef TGA Gddg eG MVQfi PcQg ef GNJdGa CbhGd eGdc hCUMGHg s
(3BNQgG (B:s
(3jfJgi GKfGA (B" (3jJcde SGgjG gd jHfi (B" s
(3bWYI efgs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdYGeI HeOjfI GdQHGW (B(3369(3c(B) s
Keywords: (3Gdabg GdeGdcjs